Patterns of Cultivating Democratic Character in Civics Learning at SMAN 3 Blitar - CHOIRUL DILLA KHUSNIAWATI; IDA PUTRI RARASATI; MINTO SANTOSO (Universitas Islam Balitar, 2024)
This research aims to determine the pattern of instilling democratic character in Civics learning at SMAN 3 Blitar. This research uses a descriptive qualitative approach. The subjects of this research were students of SMAN 3 Blitar for the 2021/2022 academic year. Data collection techniques use interviews, observation, and documentation with data analysis techniques using source triangulation and technical triangulation. The results of this research are in the form of learning process that emphasizes the cultivation of democratic character through various democratic habits. The obstacle is the lack of student activity in the learning process and student interest in learning. Efforts to resolve these obstacles include teachers providing examples in familiarizing students with democratic culture. The research results obtained were that through the process of instilling democratic character by teachers in students, students were more active and had democratic culture habits, especially in Civics learning.